ELIMINATION OF LOCAL DAMAGE TO THE PIPELINE TRENCHLESS METHOD - , В. М., Н. Ю. (Municipal economy of cities. Series: «Economy science», 2013)
The possibility of using trenchless methods of repair local damage pipelines. Analyzed promising methods for repairing sanitation sewers.